Synergistic anticancer effects of camptothecin and sotorasib in KRAS-mutated pancreatic ductal adenocarcinoma - Ramalingam, Prasanna Srinivasan; Chellasamy, Gayathri; Hussain, Md Sadique; Kodiveri Muthukaliannan, Gothandam; Hussain, Tajamul; Alrokayan, Salman; Yun, Kyusik; Mekala, Janaki Ramaiah; Arumugam, Sivakumar (Frontiers in Pharmacology, 2025)
BackgroundSotorasib (AMG510) is a first-in-class irreversible, covalent, and selective KRAS G12C inhibitor. However, in patients, acquired clinical resistance was observed within 1 year of its FDA approval. Researchers are exploring combination and repurposing strategies to help overcome this resistance and improve therapeutic efficacy. Several natural compounds have been extensively investigated for their therapeutic potential against various cancers, both individually and in combination with other chemotherapeutic agents. In this study, we examined the synergistic potential of camptothecin and sotorasib in KRAS G12C-mutated MIA PaCa-2 and KRAS G12D-mutated PANC-1 pancreatic ductal adenocarcinoma (PDAC) cells.MethodsWe assessed the half maximal inhibitory concentration (IC50) values of camptothecin and sotorasib using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and predicted their synergistic potential using combination index (CI) values and isobologram plots. Proliferation, wound healing, and colony formation assays were performed to examine the chemotherapeutic potential of camptothecin and sotorasib (combination and monotherapy). Reactive oxygen species induction, DNA fragmentation, autophagy flux, and apoptosis and cell cycle analyses were performed using 2′,7′-dichlorofluorescein diacetate (DCFH-DA), 4′,6-diamidino-2-phenylindole (DAPI), LC3-II quantification assays, and flow cytometry analysis. Furthermore, quantitative reverse transcription polymerase chain reaction (qRT-PCR) was performed to analyze gene expression patterns in both pancreatic ductal adenocarcinoma cell lines. Additionally, network pharmacology, gene ontology, and Kyoto Encyclopedia of and Genomes pathway enrichment were performed for camptothecin in PDAC.ResultsThe combination therapy with camptothecin and sotorasib resulted in significantly inhibited proliferation, migration, and colony formation; elevated intracellular ROS levels; and induced DNA fragmentation compared with monotherapies in both PDAC cell lines. Flow cytometry and cell cycle analysis revealed that the combination treatment induced apoptosis and G1/S cell cycle arrest. Furthermore, qRT-PCR analysis revealed that the combination therapy significantly upregulated pro-apoptotic genes and downregulated KRAS pathway-related genes, cleaved poly (ADP-ribose) polymerase, anti-apoptotic-related genes as well as autophagy-related genes in both PDAC cell lines. Network pharmacology analysis supports that the identified hub genes play a role in apoptosis and autophagy.ConclusionWe observed a synergistic relationship between camptothecin and sotorasib in KRAS-mutated cancer cells. Furthermore, we recommend examining more natural compounds with chemotherapeutic potential to help overcome clinical resistance of approved chemotherapeutic drugs in the near future.